AKSI KOLABORASI SELARANG MANDIRI DAN BERDAYA PROGRAM PERTAMINA PATRA NIAGA ITC - Prasadi, Oto; Christi Adi Haryanto; Yusuf Efendi; Sugiana Putri Lesrari; Ari Gunawan; Bintang Fajar Pamungkas (LPPM Akademi Manajemen Administrasi Yogyakarta, 2025)
The action program collaborative slarang independent and empowered (AKSARA MADYA) is a social and environmental responsibility program in collaboration with Barokah Community-Based Intervention in Slarang Village, which focuses on suppressing drug abuse through interventions from and for the community. This program focuses on the cultivation of laying quails and processed quail egg products. The AKSARA MADYA program also oversees the fostered group of cassava chips which are the main commodity in Slarang Village. The method in implementing this activity uses a participatory approach, forum group discussions (FGD). The results of processed quail egg products, cassava chips and other fostered products are marketed through the Butok Market in Slarang Village which uses coconut shell rounds as the rupiah exchange rate, Butok Market activities are also managed by the management board of the Cilacap Islamic Center Mosque with 5% of the profits used for humanitarian activities. The existence of processed quail eggs, cassava chips and processed seafood also produces waste in the form of egg and crab shells which are then reprocessed and used as APAR at PT Pertamina Patra Niaga ITC to reduce the use of Conventional APAR, while cassava peel waste is processed into compost by the Kutawaru Waste Bank